BUILDING BRAND LOYALTY IN K-POP ACCESSORIES : THE ROLE OF ENTERTAINMENT, INTERACTIVITY, TRENDINESS, AND EWOM - Meita Listinasari; Janice Carysa Siahaya (LPPM STIE Muhammadiah Bandung, 2025)
This research explores how entertainment, interactivity, trendiness, and electronic word of mouth (eWOM) affect brand loyalty, with brand awareness and perceived quality serving as mediating variables, within the niche market of K-Pop-themed accessories. The study applies a quantitative explanatory approach and gathers data from 112 Lookcals consumers in Surabaya using snowball sampling with analysis conducted using SPSS 22. Results reveal that brand loyalty is significantly influenced by both brand awareness and perceived quality, with perceived quality having the stronger effect. Perceived quality is significantly driven by entertainment, interactivity, and trendiness, whereas brand awareness is mainly shaped by interactivity and trendiness. eWOM shows no significant direct effect on either mediator. These findings highlight the strategic importance of product quality, trend alignment, and interactive engagement in fostering loyalty within fandom-driven markets, offering theoretical contributions to experiential marketing literature and practical insights for local brands in globalized cultural industries.